Formulasi Kebijakan: (Studi Kasus Peraturan Daerah Kabupaten Indragiri Hilir Nomor 07 Tahun 2012 tentang Bisa Baca dan Tulis Al-Qur’an bagi Murid Sekolah yang Beragama Islam) - Heru Kesumagiri; Raja Amin (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2017)
This research is based on the problems of school-age irregularities that occur due to the negative globalization has been followed and affect the life of the community, especially school-aged children in Indragiri Hilir Regency. The regional autonomy system that gives the autonomous regions the authority, authority and obligation to regulate and manage their own governmental affairs and the interests of the community both in terms of regional development and regulation of community life, in this case through the right of DPRD initiative, Commission IV of DPRD in charge of education His sense of responsibility for making regulations and guidelines for better quality management and education. By using qualitative research method, that is by explaining, describing result of research to describe an event and process and certain condition from result of collecting research data by using data collecting technique in the form of literature study to conduct study on literatures related to research title, interview ( Interview) to dig information through question and answer communication to informants or respondents from this research and by conducting documentation of documentation related to this aspect of research which then the data in the analysis by grouping, describing, researching the data to then be described And presented in descriptive form to complete the scientific work of the title of this study. The result of this research, the formulation process of policy formulation about can read Al- Qur’an long enough start from planning of Ranperda, Discussion with Executive and Legislative through 2 (two) speaking level that is high level I and II to then set And classify the mind Sheet of Indragiri Hilir regency in 2012.